2019
DOI: 10.1177/1477760619895018
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical properties of plasticized polylactic acid filament for fused deposition modelling: Effect of in situ heat treatment

Abstract: The objective of this study is to characterize the effect of in situ heat treatment on polylactic acid (PLA) and plasticized PLA during fused deposition modelling (FDM) with the motivation to improve their mechanical, thermal and physical properties. The in situ heat treatment was formed during the FDM by adjusting the bed temperature to 70°C, 90°C and 120°C. The performance of 3D, the printed samples, was compared with the compression moulded samples treated at the same temperature using a vacuum oven. PLA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The results of the study have suggested a 60% improvement in the surface roughness value whereas, the mechanical strength was not explored. Many studies in the past 5 years have been performed dealing with the in-situ treatment or post-treatment of FDM-printed specimens such as using pressure [ 26 ], cold vapor post-processing [ 27 ], and in-situ heat treatment while FDM printing of PLA specimens [ 28 ]. The increased in-situ pressure while FDM printing has tremendously improved mechanical properties by 100 to 150% for PLA samples [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study have suggested a 60% improvement in the surface roughness value whereas, the mechanical strength was not explored. Many studies in the past 5 years have been performed dealing with the in-situ treatment or post-treatment of FDM-printed specimens such as using pressure [ 26 ], cold vapor post-processing [ 27 ], and in-situ heat treatment while FDM printing of PLA specimens [ 28 ]. The increased in-situ pressure while FDM printing has tremendously improved mechanical properties by 100 to 150% for PLA samples [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased in-situ pressure while FDM printing has tremendously improved mechanical properties by 100 to 150% for PLA samples [ 26 ]. The in-situ heat treatment of PLA samples [ 28 ] was compared to heat treated sample of a vacuum oven. The results have proved that vacuum oven-based heat treatment improved mechanical strength (tensile strength 90 MPa) better than in-situ treatment (35 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise, annealing at high temperature (up to PPS's glass transition) would generate an isothermal crystallization which provides enough energy to molecular chains to have the best arrangement to form more crystalline regions and uniform lamellae. [41,57] In this work, the choice of annealing temperatures at 180, 200, and 220 C was based on this latter theory.…”
Section: Annealing Treatment and Tensile Propertiesmentioning
confidence: 99%
“…The main reason for exploring natural composite materials in the orthotics field is that these materials are mostly biodegradable, renewable, have low densities and most importantly, low production cost compared to synthetic materials, which are highly recommended for temporary applications such as an orthosis. Previous research has shown that filaments’ durability and strength using natural materials as reinforcement can be enhanced, especially when paired with PLA as the filament’s matrix (Rafie et al , 2020).…”
Section: Introductionmentioning
confidence: 99%